Relatório de estágio técnico profissional supervisionado em medicina veterinária: fomento de frangos de corte - Reginatto, Mara Keli de Almeida (2023)
The Professional Technical Internship (ETP) is an opportunity to improve and put into practice practice all the theoretical knowledge acquired during the degree in Veterinary Medicine, in the desired area of ​​professional activity. The ETP was carried out in the Development of Broiler Chickens, under the academic guidance of Professor Laura Beatriz Rodrigues, co-orientation of Veterinary Doctor Alicia Comin Pietrobiasi and supervision of Doctor Veterinarian Natana Carboni. The ETP was carried out at JBS, at the Passo Fundo unit, RS, in period from July 17th to November 14th, 2023, totaling 504 hours. Through the same, it was possible to experience the routine of extension workers, mainly related to extension rural, assisting veterinarians in their visits to poultry farms integrated producers, monitoring the implementation of company procedures and technical management guidelines given the reality of current poultry farming. Thus, the present report comprises the description of the internship location, the general activities carried out and visits carried out to promote broiler chickens. It will present a case report about the incidence of contact pododermatitis in poultry farming, and how void management health can interfere with the quality of the litter and reduce its percentage in the field. Finally, the professional technical internship was fundamental for professional and personal maturation, through the opportunity to experience experiences within poultry farming, enabling the theoretical knowledge acquired during graduation would be complemented with the routine of field. Interacting with different people, as well as accompanying professionals specialized and experienced professionals, enhances the academic’s vision of the future of the profession as a veterinarian.